IV therapy skills [ - Josephson, Dianne L. (Thomson/Delmar Learning, 2004)
Contains for the next generation of educational multimedia. Intravenous infusion therapy comes to life with this innovative tool for learning, observing and practising medication administration.IV therapy skills combines extensives facts and protocols for safe practice which are grounded in a nursing process framework. Through animated visuals, actual on screen nurse patient scenarios and unique interactive functionality, this program is by far the most rounded approach to IV therapy procedures ever made available.